Prevalensi Pneumonia Nosokomial pada Pasien Rawat Inap di ICU RSUD Dr. Moewardi Periode April-Mei 2012 - Gultom, Krismawarni; Prasodjo, JB; Hudiyono, . (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background : Infectious diseases are the main causes of morbidity and mortality in the world. The prevalence of nosocomial infections still high in development countries. Nosocomial infections often occured, especially in ICU’s patients, it is around 25-33%. A minimum research of the incidence of hospital acquired pneumonia in Dr. Moewardi Hospital is the background of this research. Thorax photo were obtained when the patient first entered the hospital and after being treated in hospital for more than 48 hours. It used as one of the diagnostic tests to assist the prevalence of hospital acquired pneumonia on ICU’s patient. Methods : This is a descriptive observational research method with a cross-sectional approach to obtain the prevalence of hospital acquired pneumonia in ICU Dr. Moewardi Hospital during April-May 2012. The sample is done by using a purposive sampling. The population of this study was all patients who are hospitalized in the ICU Dr. Moewardi Hospital in Surakarta during April-May 2012. Results : Total sample are 72 patients. The result of this research shows that the prevalence of hospital acquired pneumonia in April-May 2012 on patients who are hospitalized in the ICU Dr. Moewardi Hospital is 8.3%. The middle age group (48-64 years) and old age (65-88 years) are the greater group of getting risk of hospital acquired pneumonia. Discussion : The prevalence of hospital acquired pneumonia is 8.3%. This may be caused by the use of respiratory mechanic devices, the immunocompromised patients, hospital environmental factors, the use of immunosuppressive drugs and the time of patients hospitalized. It is recommended that all of medical team of this hospital need to develop an effective program to control and prevent nosocomial pneumonia infection. Key words : prevalence, hospital acquired pneumonia, thorax photo